1995
DOI: 10.1038/bjc.1995.355
|View full text |Cite
|
Sign up to set email alerts
|

Post-operative levamisole may compromise early healing of experimental intestinal anastomoses

Abstract: Summary There exists growing interest in immediate post-operative local adjuvant therapy after resection of intestinal malignancies. It is therefore necessary to assess its potential effect on the healing of intestinal anastomoses. Five groups (n = 20) of rats underwent resection and anastomosis of both ileum and colon: a control group and four experimental groups receiving intraperitoneal 5-fluorouracil (5-FU), 5-FU plus leucovorin, 5-FU plus levamisole or levamisole alone, on the day of surgery and the next … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 24 publications
1
38
0
Order By: Relevance
“…The bursting site was noted. The breaking strength of the segment, as a measure of the resistance to longitudinal forces, was measured immedi ately after determination of the bursting pressure [27], The segment was placed in a tensiometer that provided a constantly increasing distraction, The peak force (in g) necessary to induce total disruption of the segment was taken as the breaking strength. The breaking site was noted.…”
Section: 4 Analytical Proceduresmentioning
confidence: 99%
“…The bursting site was noted. The breaking strength of the segment, as a measure of the resistance to longitudinal forces, was measured immedi ately after determination of the bursting pressure [27], The segment was placed in a tensiometer that provided a constantly increasing distraction, The peak force (in g) necessary to induce total disruption of the segment was taken as the breaking strength. The breaking site was noted.…”
Section: 4 Analytical Proceduresmentioning
confidence: 99%
“…Cytostatic drugs are by nature anti-proliferative and may therefore be expected to interfere with wound healing. Indeed, 5-FU administered daily from the day of operation onwards until sacrifice after 7 days severely impairs anastomotic healing in the rat intestine (Graf et al, 1992;de Waard et al, 1995b). In earlier experiments, we tried to mitigate this negative effect by concomitant administration of either interleukin 2 or granulocytemacrophage colony-stimulating factor, but 5-FU impaired repair was not essentially altered by either cytokine.…”
Section: Discussionmentioning
confidence: 99%
“…The validity of this procedure has been confirmed in a pilot experiment. Anastomotic breaking strength was compared in two groups of rats, either measured directly or after the procedure used for measuring the bursting pressure, and found to be similar in both groups (de Waard et al, 1995b). The anastomotic segment was then cleaned from the surrounding tissue and a 5 mm segment with the suture line in the middle was collected.…”
Section: Analytical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…During the first postoperative days, wound strength is considered to solely depend on the suture-holding capacity of the existing collagen fibrils (27). From 3 h to 4 days after the operation, the absolute and the relative collagen synthesis steadily increases (26,28), providing evidence that an anastomosis strength increases from the beginning of wound healing, and the risk of anastomotic leakage decreases. The role of intubation in the healing of anastomosis is controversial, as a previous study demonstrated that an indwelling catheter traversing the anastomosis slows down the healing process in that segment (29).…”
Section: Intubation -------------------------------------------------mentioning
confidence: 94%